2019
DOI: 10.1016/j.jfma.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and predicting factors for diabetic macular edema treated with ranibizumab – One-year real-life results in Taiwan

Abstract: Compared with existing prospective studies, the one-year real-life data in Taiwan showed fewer ranibizumab injections for DME and a less prominent yet still significant visual improvement. Both visual and anatomical improvements at Month 3 were correlated with the level of improvements at Month 12. Previous subtenon steroid injection might reduce the need of additional ranibizumab injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 26 publications
6
32
0
1
Order By: Relevance
“…5 Suboptimal results with fewer injections were also reported in subsequent real-world studies conducted on different diseases, such as DME 6,7 and RVO. 8 However, results comparable to those in clinical trials were found when similar treatment schedules were used in AMD and DME. 9,10…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…5 Suboptimal results with fewer injections were also reported in subsequent real-world studies conducted on different diseases, such as DME 6,7 and RVO. 8 However, results comparable to those in clinical trials were found when similar treatment schedules were used in AMD and DME. 9,10…”
Section: Introductionsupporting
confidence: 54%
“…Nonetheless, the evidence on the relationship between average treatment intensity and average visual outcomes at the centre level is substantial. 4,5,8,9…”
Section: Rationale For the Two Indicatorsmentioning
confidence: 99%
“…These findings are consistent with previous analyses of real-world anti-VEGF treatment patterns, which have similarly reported average 12-month injection frequencies of 4.3-5.8 and 2.2-4.4 among patients with nAMD and DME, respectively. 24,25,[33][34][35][36][37][38] Our results also agree with American Society of Retina Specialists Preferences and Trends Surveys, which suggest that most retina specialists prefer to administer ongoing treatment according to anatomic findings observed on follow-up optical coherence tomography (e.g., subfoveal retinal thickness and central subfield thickness), rather than FDA labeling. 21,22 However, these findings are not intended to suggest that real-world injection frequencies reflect patient need or response to therapy.…”
Section: Real-world Dosing Versus Labeled Injection Schedulessupporting
confidence: 84%
“…Moreover, the greatest increases in both BCVA and CRT were observed after 3 monthly loading injections. Protocol I from Diabetic Retinopathy Clinical Research (DRCR) and research by Lai et al had similar results in demonstrating that BCVA restoration after the 3 monthly injections was predictive of long-term visual benefits (12,17).…”
Section: Discussionmentioning
confidence: 82%
“…Despite robust findings from clinical trials, around half of eyes do not fully respond to anti-VEGF (9), and further exploration of prognostic factors associated with better visual outcomes is warranted. Age, HbA1c status, central retinal thickness (CRT) have been investigated but to mixed results (10)(11)(12)(13). Moreover, little is known regarding how optical coherence tomography (OCT) biomarkers including epiretinal membrane (ERM) and ellipsoid zone disruption (EZD) affect the resolution of macular edema and final vision, and its implication for therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%